Integration of leaf gauge technique in the digital fabrication of stabilization splint for temporomandibular disorder: A case report - Ricca Chairunnisa; Alexander Justin; Syafrinani (Indonesian Journal of Prosthodontic, 2025)
AbstractBackground: Temporomandibular disorder (TMD) is a multifactorial musculoskeletal condition characterized by jaw pain, limited mandibular movement, and joint sounds. A common subtype is disc displacement with reduction (DDWR), often accompanied by local myalgia and arthralgia. Stabilization splints are a standard treatment modality, with 3D printing offering benefits such as precision, efficiency, and reduced clinical time. However, the effectiveness of splint therapy depends on accurate recording of the mandibular-maxillary relationship, which can be reliably achieved using a leaf gauge.Objective: To report the management of a TMD case involving DDWR, myalgia, and arthralgia in an adolescent patient using a leaf gauge to establish centric relation during the fabrication of a 3D-printed stabilization splint.Case Report: An 18-year-old male presented with right-sided jaw pain and clicking upon mouth closure. History revealed parafunctional habits, including unilateral mastication and academic stress. Diagnosis was confirmed via DC/TMD Axis I and II, along with clinical and radiographic assessment, indicating DDWR with myalgia and arthralgia. Treatment includes behavioral treatment, infrared light therapy, and fabrication of a stabilization splint. Centric relation was determined using a leaf gauge to ensure accurate mandibular positioning.Conclusion: The use of a leaf gauge in this case facilitated precise centric relation, enhancing the efficacy of the 3D-printed stabilization splint. This approach contributed to significant symptom improvement and underscores the value of integrating analog tools within digital workflows in TMD management.Keywords: disc displacement with reduction, leaf gauge, 3D printing, local myalgia, arthralgia